Predicting most productive requirements elicitation teams using MBTI personality traits model - Iqbal, M. Aqeel; Shah, Asadullah; Karamat Khan, Tehmina (Blue Eyes Intellegent Engineering & Services Publications, 2019)
The social and collaborative nature of requirements elicitation process bases its core dependency on aptitude, attitudes, and personality characteristics of its participants. The participant's personality characteristics are directly related with their personality traits, which can be categorized using different model has been used successfully for the assessments of personality of software engineers since last few decades. In this article, the personality traits for requirements elicitation teams have been predicted using MBTI personality assessments model, on the basis of their industry demands job descriptions/tasks and major soft skills. The article presents a complete personality prediction process using a systematic approach based on major soft skills mapping with job descriptions, personality attributes and personality. The obtained results show that extroversion and feelings personality traits are the most suitable assigned the task of requirements elicitation. The obtained results are very much aligned with the already published scholar's work for software engineer's personality assessments and development team composition.